2021
DOI: 10.3389/fpubh.2021.774572
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception Measurement and Influencing Factors of COVID-19 in Medical College Students

Abstract: Purpose: In China, the coronavirus disease 2019 (COVID-19) pandemic has been under control and entered the normal prevention and control stage. For medical college students, many studies have analyzed their knowledge, risk perception, and prevention behaviors of COVID-19, but only a few pieces of research explore the content structure of COVID-19 risk perception and the influencing factors. This study measured the students' risk perception of COVID-19 and its dimensions and analyzed the influencing factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
9
1
1
Order By: Relevance
“…This indicates the importance of health education that could improve prevention behavior toward covid-19 in society. 32 Regarding risk perception about covid-19, contrary to other studies reporting positive risk perceptions, 33,34 this study identified that students were afraid of getting infected and infecting their loved ones. This implies that college students may be more concerned about their parents and other older family members than about themselves, an aspect that has been seen in another study.…”
Section: Discussioncontrasting
confidence: 55%
“…This indicates the importance of health education that could improve prevention behavior toward covid-19 in society. 32 Regarding risk perception about covid-19, contrary to other studies reporting positive risk perceptions, 33,34 this study identified that students were afraid of getting infected and infecting their loved ones. This implies that college students may be more concerned about their parents and other older family members than about themselves, an aspect that has been seen in another study.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the presence of words such as ‘hesitancy’, ‘barriers’, and ‘refusal’ in the literature regarding COVID-19 vaccination demonstrates the clear problems of COVID-19 vaccine approval among the young medical community. It was shown that almost all Russian medical students believed that COVID-19 was a serious disease (89.3%) and expressed profound concern about the current epidemiological situation (89.9%), sounding similar to the common understanding of the situation among medical students from around the world; vaccination importance was recognized by most of the respondents in the known studies, reaching 73.2–99.4% [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 89%
“…According to recent studies, the understanding of the importance of the COVID-19 vaccine among medical students all over the world is very high, since COVID is a potentially severe acute respiratory infection [ 28 , 36 , 37 , 38 , 39 ]. However, the presence of words such as ‘hesitancy’, ‘barriers’, and ‘refusal’ in the literature regarding COVID-19 vaccination demonstrates the clear problems of COVID-19 vaccine approval among the young medical community.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, those who perceived their financial conditions as wealthy were more likely to be optimistic. Participants whose household economy was wealthy probably did not need to worry about medical expenditure and their life after contracting COVID-19; therefore, they became more optimistic about infection probability ( Alicea-Planas et al, 2021 ; Qin et al, 2021 ). Engaging in paid work was also positively associated with pessimism about infection probability in this study, although some previous research found that unemployed people were more likely to experience psychological symptoms than employed people at the beginning of the COVID-19 outbreak ( Xiong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%